2021
DOI: 10.1507/endocrj.ej20-0577
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-lowering effects of 7-day treatment with SGLT2 inhibitor confirmed by intermittently scanned continuous glucose monitoring in outpatients with type 1 diabetes. A pilot study

Abstract: The present study used intermittently scanned continuous glucose monitoring (isCGM) in 10 patients with type 1 diabetes mellitus (T1DM) to evaluate the efficacy and safety of 7-day outpatient treatment with the combination of intensive insulin therapy and sodium-glucose transporter 2 inhibitor (SGLT2-I). All participants wore isCGM and were treated with either 50 mg/day ipragliflozin or 5 mg/day dapagliflozin. The primary outcome, percent time with glucose at 70-180 mg/dL (TIR: time in range), improved signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…Regarding the secondary endpoints, we showed that the ipragliflozin treatment significantly decreased the participants' required insulin dose and significantly improved their glycaemic control (decrease in HbA1c and increase in TIR) and their glycaemic variability (decreases in SD, CV% and MAGE) without increasing TBR, as reported in several studies 7,9,11–13 …”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Regarding the secondary endpoints, we showed that the ipragliflozin treatment significantly decreased the participants' required insulin dose and significantly improved their glycaemic control (decrease in HbA1c and increase in TIR) and their glycaemic variability (decreases in SD, CV% and MAGE) without increasing TBR, as reported in several studies 7,9,11–13 …”
Section: Discussionsupporting
confidence: 72%
“…Regarding the secondary endpoints, we showed that the ipragliflozin treatment significantly decreased the participants' required insulin dose and significantly improved their glycaemic control (decrease in HbA1c and increase in TIR) and their glycaemic variability (decreases in SD, CV% and MAGE) without increasing TBR, as reported in several studies. 7,9,[11][12][13] The association between increased glucagon and glycaemic stabilization in persons with T1D who are treated with SGLT2 inhibitors is not fully understood. In a recent study, dapagliflozin treatment did not significantly increase the counter-regulatory glucagon response to a hypoglycaemic clamp protocol, but it increased fasting glucagon levels when normoglycaemia was present in subjects with T1D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations